The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/03009742.2016.1249941
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular function at two-year follow-up in treatment-naive rheumatoid arthritis patients is associated with anti-cyclic citrullinated peptide antibody status: a cohort study

Abstract: Deformation analysis by speckle-tracking echocardiography is a valuable tool to detect early development of myocardial dysfunction despite normal ejection fraction in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
1
20
0
3
Order By: Relevance
“…We found that patients with high anti-CCP titres were more prone to decreased myocardial function. 29 This in agreement with the observation that the citrullinated proteins are increased in the myocardial interstitium of patients with RA because these proteins are associated with the amount of interstitial fibrosis. 30 Moreover, a recent study on permeabilized cardiomyocytes demonstrated that citrullination per se can impair contractility by reducing myofilament Ca 2+ sensitivity.…”
Section: Is Rheumatoid Arthritis Associated Withsupporting
confidence: 90%
“…We found that patients with high anti-CCP titres were more prone to decreased myocardial function. 29 This in agreement with the observation that the citrullinated proteins are increased in the myocardial interstitium of patients with RA because these proteins are associated with the amount of interstitial fibrosis. 30 Moreover, a recent study on permeabilized cardiomyocytes demonstrated that citrullination per se can impair contractility by reducing myofilament Ca 2+ sensitivity.…”
Section: Is Rheumatoid Arthritis Associated Withsupporting
confidence: 90%
“…Moreover, a high anti‐CCP antibody titer offered an independent risk factor for severe plaque. According to non‐invasive methods with conventional echocardiography, a recent study has described the association between ventricular deformation and anti‐CCP antibody levels in patients with RA . However, to the best of our knowledge, this is the first study to clarify the association between severity of carotid atherosclerotic plaque and high anti‐CCP antibody titers in patients with RA.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of CAC progression seems to be also higher in RA patients than in the general population . The presence of CAC in newly diagnosed RA patients has also been shown and these had a small progression rate during a 2 year follow‐up period …”
Section: Introductionmentioning
confidence: 92%
“…19 The presence of CAC in newly diagnosed RA patients has also been shown and these had a small progression rate during a 2 year follow-up period. 20 It is unclear how the pathophysiologic mechanisms involved in RA, such as chronic systemic inflammation or bone metabolism disturbances, may be associated with coronary disease progression and calcification. Previously, different proinflammatory cytokines, such as tumor necrosis factor-α and interleukin-6, 21 and postulated mediators of vascular calcification, such as osteoprotegerin (OPG), 22 have been associated with the severity of CCS in RA patients.…”
Section: Introductionmentioning
confidence: 99%